From Perception to Adoption: Drivers of Commercial Health Insurance Purchase Intentions Among School Teachers in Nepal - Biswakarma, Gangaram; Dhakal, Basanta; Sapkota, Daya (Journal of Innovation in Academia, 2025)
The study aims to identify the determinants of commercial health insurance purchase intention among uninsured school teachers in Nepal. The study adopted a cross-sectional survey study of 412 uninsured school teachers. PLS-SEM approach has been adopted for the analysis. Purchase intention for commercial health insurance among school teachers is primarily affected by perceived usefulness and attitudes, along with the norms, literacy, and the service quality influence as supporting factors. This suggests that for enhancing adoption and long-term engagement, benefit-focused communication and product designs, added with trust and retention efforts, are essential. While male and female teachers differ somewhat in average views, these differences do not meaningfully change how the key drivers relate to intention.